Youth justice critical readings - Muncie, John; Hughes, Gordon 1952-; McLaughlin, Eugene 1959- (SAGE in association with the Open University, 2002)
Youth Justice: Critical Readings brings together for the first time the most influential international contributors to the emergent field of youth justice studies. This will be an essential sourcebook for students and teachers in the fields of criminology, youth studies, criminal justice, social work and social policy as well as for practitioners and managers in this increasingly important field of professional practice.